The Protections Against Domestic Violence Survivors under the Penal Code in Malaysia - Abdul Rahim, Asmar; A. Rahman, Aspalella; Md Ismail, Che Thalbi; Mahdzir, Nazli (2018)
Domestic violence is a serious offence and more common than most people realize. This problem is often seen as a gender issue where women are more prone to be the victims of assaults compared to men. The victims suffered multiple forms of abuse but psychological abuse remains as the most common form of domestic violence. In combatting this problem, Malaysia has passed the Domestic Violence Act (Act 521) in 1994 (DVA 1994). The DVA 1994 must be read together with the Penal Code (Act 574) (PC) or any other written law involving offences relating to domestic violence. The objective of this paper is to analyse the legal protection available to domestic violence under the PC. Thus, provisions relating to offences against person under the PC will be examined. victim where offences where force or violence is threatened or directed against a person under the PC namely Section 351 (assault), Section 350 (criminal force), Section 319 (hurt) and Section 320 (grievous hurt). By applying a descriptive and analytical approach in data analysis, the study found that the survivors of domestic violence in Malaysia are well protected under the PC which becomes the platforms for them to bring the perpetrator to the court. However the offences and punishments available are subject to the degree of injury suffered and evidence produce by the victims. Unfortunately the legal protection becomes fertile, if the survivors refuse to bring the perpetrators to the court due to some barriers faced by them